Features of translation of the names of Kazakh national dishes in the epic novel “The Path of Abai” into Persian - Б.Ш., Бaтырхaн; Д.Е., Әшімхан (Journal of Oriental Studies, 2019)
The article examines the problem of translating the names of national Kazakh dishes that are found in the epic novel by Mukhtar Auezov, “The Path of Abay”, into Persian. The names of Kazakh dishes, as well as methods for their translation into Persian were analyzed in this article. Based on this analysis, an attempt was made to determine the most successful translation of the considered examples. Along with this, the names of Kazakh national dishes found in the epic novel "The ay of Abai", by which method are translated hen translating into Persian, the names of Kazakh national dishes were translated using transliteration and transcription methods. hen studying the translation of the epic novel “The Abay ay” into Persian, we paid attention to the national dishes encountered and translated them into the target language. As a result, we came to the conclusion that the translation should be carried out by people who are fluent in the language of the original and the translation, and also have great knowledge in the field of national culture, traditions and mores of the people from whose language the original work is translated. The novel-epic was translated into Persian by N. Asgarzade, however, he did not translate from the original language, but from the Russian version, therefore, the inaccuracies that existed in the Russian translation automatically turned into the text of the Persian translation. Thus, we were once again convinced that translation into any language should be carried out directly from the text of the original, otherwise it is impossible to guarantee a high-quality translation . Key words: «The Path of Abai», the names of national dishes, Persian, culture-specific items, translation of culture-specific items.